A full evaluation for the enantiomeric impacts of lactofen and its metabolites on aquatic macrophyte Lemna minor. (15th September 2016) - Wang, Fang; Liu, Donghui; Qu, Han; Chen, Li; Zhou, Zhiqiang; Wang, Peng
Abstract: Pesticide pollution of surface water represents a considerable danger for the aquatic plants which play very crucial roles in aquatic system such as oxygen production, nutrient cycling, water quality controlling and sediment stabilization. In this work, the toxic effects of the chiral herbicide lactofen and its three metabolites (desethyl lactofen, acifluorfene and amino acifluorfene) to the aquatic plant Lemna minor ( L. minor ) on enantiomeric level were evaluated. The influences on growth rate, fresh weight, content of photosynthetic pigment, protein and malondialdehyde (MDA) and the activities of antioxidant defense enzymes (catalase (CAT) and superoxide dismutase (SOD)) were measured after 7 days of exposure. L. minor growth was inhibited in the order of (S)-desethyl lactofen > racemic-desethyl lactofen > (R)-desethyl lactofen > racemic-lactofen > (S)-lactofen > (R)-lactofen > acifluorfene > amino acifluorfene, and the IC50 (7d) values showed desethyl lactofen was the most powerful compound which was about twice as toxic as lactofen. The contents of chlorophylls (Chl) and carotenoids (Car) were significantly reduced by the chemicals, while, the levels of protein, MDA and the activity of CAT and SOD enzymes increased in most cases. The obtained results revealed that lactofen and its metabolites had an undesirable effect on L. minor, in terms of physiological and biochemical aspects. Besides, enantioselective toxicity of lactofen and desethyl lactofen to L. minor was observed. The S-enantiomer of desethyl lactofen was more toxic than the corresponding R-enantiomer. Furthermore, racemic lactofen was more toxic than the individual enantiomers. The side effects of pesticide metabolites and the enantioselectivity should be considered in developing optically pure products and risk assessment. Graphical abstract: Highlights: Impacts of lactofen and its three main metabolites to Lemna minor was investigated. Enantioselectivity of the enantiomers of lactofen and the metabolite was found. The primary metabolite desethyl lactofen was more toxic to Lemna minor than lactofen.